Consumption and consumers’ quality perceptions of poultry products in Algeria - Benamirouche, Karima (2026)
Introduction. The remarkable growth of poultry production and consumption in recent years has increased consumers’ attention to product quality and safety. Thus, understanding their perceptions is crucial for promoting the sector’s sustainable growth. Objective. To evaluate chicken meat and offal consumption among Algerian consumers and determine their quality perceptions, with particular attention to concerns about chemical contaminants. Materials and methods. This study was conducted in Algeria between July and September 2023. Data were collected through a non-probability online survey of 1,064 consumers. Information was gathered on chicken meat and offal consumption, factors affecting consumption, and knowledge of chemical contaminants. Differences in consumption frequencies were analyzed using a chi-square test. For numerical variables, the Shapiro-Wilk test was used to examine data normality. Results. Almost all the study population consumed chicken meat (>92 %), while only about half consumed chicken offal. Children showed the lowest consumption (30 %). Price and quality were the most important factors affecting the consumption of poultry products. In addition, 55.92 % of participants reported being aware of contaminants, with antibiotics being the most frequently mentioned substances. However, 41.34 % of respondents who were aware of contaminants had not reduced their consumption due to product prices and limited availability of alternatives. Approximately 80 % of respondents were willing to purchase antibiotic-free poultry products. Conclusions. The findings highlight the widespread consumption of chicken. Although consumers were aware of chemical contaminants, chicken remained an important source of animal protein due to limited alternatives, highlighting the need for strategies to strengthen food safety practices and maintain consumer trust.